DAMPAK UKURAN PERUSAHAAN, PROFITABILITAS, SOLVABILITAS, UMUR PERUSAHAAN, DAN UKURAN KAP TERHADAP AUDIT DELAY PADA PERUSAHAAN CONSUMER GOODS - Ni Luh Putu Sandrya Dewi; Ni Putu Yuria Mendra; Ni Putu Mesia Wandari (UNHI Press, 2024)
The annual report must be submitted on time and audited by a public accountant to ensure the correctness of the company's annual report according to the company's actual performance. A late annual report will have an impact on delays in the company's annual announcement. The longer the time required, the longer the audit delay. The research aims to examine the influence of firm size, profitability, solvency, company age, and KAP size on audit delay in consumer goods companies listed on the Indonesia Stock Exchange in 2020–2022. The population of this research is consumer goods companies listed on the Indonesia Stock Exchange in 2020–2022, namely 82 companies. The sample in this research was determined based on the purposive sampling method, and a sample of 52 companies was obtained with a research period of 3 years, so the total observations were 156. The analysis technique used in this research is the multiple linear regression analysis technique. The research results show that profitability and KAP size have a negative effect on audit delay, while firm size, solvency, and company age have no effect on audit delay.